GUIDED INQUIRY-BASED LEARNING OF TRIGONOMETRIC IDENTITIES - Bernido, Ryan B; Boyon, Carolina L (PEOPLE: International Journal of Social Sciences, 2020)
The implementation of K-12 basic education curriculum brought some concerns in the educational sector of the Philippines such as shortage in teaching and learning materials, and the required teaching-learning approach that would cater for the development of 21st century skills among learners. This study developed and validated guided inquiry-based learning materials in understanding the trigonometric identities in Grade 11 Pre-calculus to promote self-directed, independent, and inquiry-based learning, and to verify its effects in student learning. The guided inquiry-based learning materials underwent evaluation and validation, and were evaluated as Highly Acceptable to teachers and students. This study utilized the descriptive method using the 7-point scale. Quasi-experimental design was adopted to measure the effects of the validated learning materials and the use of inquiry-based learning in student’s performance. Results confirmed that students are equally able to develop cognitive skills in trigonometric identities through IBL and conventional learning modality. Thus, the validated guided inquiry-based materials developed and used in this study can be adopted in its original form to promote 11th graders’ self-directed, independent, and inquiry learning necessary for developing 21st century skills such as critical thinking.